Motivational Factors for Becoming a Teacher among Economics Education Students from Rural and Urban Areas - Jayanti, Intan; Noviani, Leny; Sabandi, Muhammad (FKIP Universitas Lampung, 2023)
Motivational Factors to Become Teacher in Economic Education Students from Villages and Cities. Objective: Research was conducted to determine differences in motivation factors to become teachers among Economic Education students in Central Java based on place of residence. Method: The research sample was 149 students from the UNS, UNNES and UNSOED Economic Education Study Program who had undertaken internships at schools. Test analysis technique uses Independent Sample T-Test. Findings: The research results show a significance value of 0.00, less than 0.05. This means, there are different factors that motivate rural and urban students to pursue a career as teachers because socio-cultural differences. Conclusion: There level of prospective teachers from villages who are superior in all motives (intrinsic, extrinsic and altruistic). The social dissuasion indicator for urban teacher candidates is higher, while the indicators salary, high demands, career fallback, teaching and learning experience the exhibit similar levels for all respondents. Keywords: teacher, motivation, city,village.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202336